Antimicrobial activities against multidrug resistant and foodborne organisms and acute toxicity study of peperomia pellucida (ketumpang air) aerial part extracts - Zamri, Nurul Alia Farhah Mohd (2018)
Peperomia pellucida has been used in ethnomedicines for the treatment of various illnesses. However, the scarcity of scientific informations on its antibacterial potential and safety concern have enhanced the urgency of conducting this study. The aims of the current work were to evaluate the in vitro antibacterial activities of methanol and aqueous extracts of P. pellucida aerial part (PPAP) against multi-drug resistant organisms (MDROs) (Study I) and foodborne pathogens (Study II). Further, the best extract was tested for in vivo acute toxicity in Study III. The MDROs tested in Study I involved Methicillin-Resistant Staphylococcus aureus (MRSA), Vancomycin-Resistant Enterococcus (VRE), Extended Spectrum Beta-Lactamase (ESBL) and Carbapenem- Resistant Enterobacteriaceae (CRE). Whilst in Study II, the foodborne pathogen strains examined including Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella typhimurium. Both studies applied similar methods of testing where the antibacterial potentiality of the plant extracts were evaluated at two concentrations (250mg/ml and 500mg/ml) using Kirby-Bauer's disk diffusion assay. Only bacteria that showed susceptibility were further determined for Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) using microbroth dilution method. Findings obtained indicated that the preliminary screening of the inhibition zone depicted that all bacteria strains were resistant to P. pellucida aqueous extract. In contrast, only P. pellucida methanol extract was found to be a potent inhibitor towards Bacillus cereus. From this initial screening, Bacillus cereus was subsequently subjected to MIC and the bacteria activities was inhibited at 3.91mg/ml of P. pellucida methanol extract. Additionally, the MBC of this plant extract was 7.81mg/ml. Study III, in contrast, was conducted to investigate the effects of a single dose of 5000mg/kg PPAP methanol extract on female Sprague Dawley rats by adopting the OECD guidelines No 425. Results acquired from Study III revealed that there were neither mortality nor morbidity and absent of abnormalities on the physical appearances and behaviour of all the rats examined. Likewise, the gross examination displayed normal condition of all orifices, cranium, thorax, abdomen cavities and visceral organs within. The body weight, food consumption and organ weight were also looked comparable. Taking all the cumulative data together, this study suggests that PPAP methanol extract would be a promising source to inhibit B. cereus growth in foods but it only displayed weak antibacterial activities against other tested MDROs and foodborne pathogens. In vivo, the approximate acute median lethal dose (LD50) of PPAP methanol extract in female rats was estimated to be higher than 5000mg/kg.